Radiative effects and chemical compositions of fine particles modulating urban heat island in Nanjing, China. (15th February 2021) - Wu, Hao; Wang, Tijian; Wang, Qin'geng; Cao, Yang; Qu, Yawei; Nie, Dongyang
Abstract: Particulate matter with aerodynamic diameters no greater than 2.5 μm (PM2.5 ) affects solar radiation through direct and indirect means, and the effects vary with different compositions. The heterogeneous distributions of the concentration and compositions of PM2.5 between the urban centre and the suburban areas lead to changes in the urban heat island (UHI) intensity. This study investigated the direct and indirect effects of PM2.5 and the impact of scattering and absorption by PM2.5 on UHI intensity in Nanjing, China, using numerical modelling. The results showed that both the direct and indirect effects of PM2.5 reduced the UHI intensity (approximately between 0.04 K and 0.07 K) during the daytime and strengthened it during the night-time (approximately between 0.05 K and 0.08 K). Furthermore, scattering and absorbing compositions have a comparable impact on UHI where the concentration of scattering compositions is nine times the concentration of the absorbing compositions. They both decreased UHI intensity during the daytime (up to approximately 0.1 K) and increased it during the night-time (up to approximately 0.12 K). The existence of absorbing compositions of PM2.5 and their high concentrations may have worked in tandem to mask the UHI phenomenon and other problems encountered in urban development in the last few decades. Graphical abstract: Image 1 Highlights: PM2.5 affected solar radiation through direct and indirect ways. Inhomogeneous distribution of PM2.5 between the urban and suburban areas influences urban heat island (UHI). Direct and indirect effects of PM2.5 reduced the UHI intensity during daytime and strengthened it during night-time.